The study of head/disk interfacial behavior in PZT glide tests - Zheng, Zheng. (2008)
The project is a study of the glide head/ bump disk interfacial behavior in the glide calibration and the glide test. The purpose is to find out a method to improve the reproducibility of the glide test. The Bump Avalanche Test, which uses the calibrated glide head and pre-characterized bump disk, is introduced.